The Effect of Metaphylactic Use of Tildipirosin for the Control of Respiratory Disease in Long-Distance Transported Dairy Calves - Celestino, Maria Luiza; Fernandes, Leticia; Menta, Paulo Roberto; Paiva, Daniela; Ribeiro, Thiago Lauro; Silva, Thiago; Bilby, Todd R.; Neves, Rafael C.; Ballou, Michael A.; Machado, Vinicius S. (Frontiers in Veterinary Science, 2020)
The objective of this study was to evaluate the efficacy of two metaphylactic strategies using tildipirosin for the control of bovine respiratory disease (BRD) in dairy calves transported to a heifer raising facility within their first week of life. A total of 2,100 calves were enrolled in the study. Animals were transported for approximately 1,715 km, from dairies located in Minnesota to a calf raising facility located in New Mexico, where they were housed in individual hutches until weaning. Three days after arrival, calves were randomly allocated into three groups: 1) META1: single subcutaneous (SQ) injection of tildipirosin (ZuprevoTM, Merck Animal Health) at enrollment at 4 mg/kg; 2) META2: SQ injection of tildipirosin at enrollment and injection 17 days later; 3) CON: untreated controls. The BRD incidence was 11.4%, 10.8% and 9.4% for calves enrolled in the CON, META1 and META2, respectively (P = 0.44). Lung lesions diagnosed through ultrasonography was found in 21.0%, 21.0%, and 21.8% of calves enrolled in CON, META1, and META2, respectively (P = 0.99). Mortality tended to be greater for CON calves in comparison to META2 calves (1.5% vs 0.6%, P = 0.06), but did not differ between calves enrolled in CON and META1 groups (1.5% vs 1.2%, P = 0.55). Growth was not affected by metaphylaxis. The average daily gain for calves enrolled in CON, META1, and META2 was 517, 518 and 525 g, respectively (P = 0.25). Blood analysis revealed that some of the markers of inflammation assessed were influenced by metaphylaxis. At 27 days after enrollment, META2 calves had decreased concentrations of haptoglobin, serum amyloid A, and aspartate aminotransferase, compared to CON calves (P < 0.05). Additionally, CON calves had increased concentrations of globulins and lower albumin to globulin ratio than META2 calves at the end of the weaning period (P < 0.05). In conclusion, tildipirosin metaphylaxis did not decrease the incidence of BRD nor did it have an impact on weight gain. However, metaphylaxis with two injections of tildipirosin at enrollment and 17 days later tended to reduce mortality and improved the systemic inflammatory status of calves during the preweaning period.